PENGARUH DIGITAL MARKETING DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DENGAN BRAND IMAGE SEBAGAI VARIABEL MEDIASI (Studi Pada Konsumen Wingko Babat Pak Moel di Kota Semarang) - Rachma Putri; Bambang Munas Dwiyanto (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Many companies are trying to recover their product sales after the pandemic. Especially these days where the business world is competitive, all companies must be able to innovate in increasing product sales and expanding market share. Digital marketing is one of strategies used by the company to introduce and market the products, also to establish communication with consumers. In addition, word of mouth can also be referred as a medium to spread accurate and reliable information that can build curiosity from other people's recommendations for a product or service. The combination of these two strategies is considered capable of forming a company's brand image if done well, which then has an impact on consumer purchasing decisions in the future. This study aims to analyze the influence of digital marketing and word of mouth on purchase decision through brand image as the mediating variable of Wingko Babat Pak Moel consumers in Semarang, so it can be a review material for Wingko Babat Pak Moel to increase their product sales and expand their market share. The population of this research is the consumers of Wingko Babat Pak Moel in Semarang City who have bought the product within one year. The data obtained through a questionnaire as many as 147 respondents were then analyzed using the AMOS 24.0 program. The results of this study indicate that Digital Marketing and Word of Mouth used as Wingko Babat Pak Moel's marketing strategy have a positive influence on Brand Image and Purchase Decisions. Then, Brand Image also has a positive influence on Purchase Decisions